An Infodemic of Misinformation on Stem Cell Therapy Among the Population of Saudi Arabia: A Cross-Sectional Study - Aboalola, Doaa; Badraiq, Heba; Alsiary, Rawiah; Zakri, Samer; Aboulola, Neda; Haneef, Loay; Malibari, Dalal; Baadhaim, Moayad; Alsayegh, Khaled (Frontiers in Medicine, 2022)
In recent years, the industry of unproven stem cell-based therapies has been on the rise round the globe, putting patients at great risk of potential harm. In this cross-sectional study, we aimed to assess the level of knowledge and awareness of the general public (including patients and/or their relatives) in Saudi Arabia on stem cell therapy and to assess the degree of willingness to try stem cell-based treatment options, should it be offered to them. Methods: A voluntary questionnaire of 16 questions was distributed randomly through social media outlets. Results: 2030 individuals participated in the survey. A total of 1292 (63.6%) stated that they would accept stem cell therapy or would recommend it to their friends and relatives. Alarmingly, 72.1% of participants were unaware that using unapproved stem cell-based treatments may lead to serious health complications including cancer. More than 20% believed that stem cell therapy is already approved for organ/tissue regeneration. Worryingly, 60.6% of the physicians and 56.4% of the medical students stated that they would recommend stem cell treatment for their patients. Conclusions: There is a concerning spread of misinformation among the Saudi population, including physicians, regarding stem cell therapy. This calls for a targeted effort to raise awareness about the current status of stem cell treatment in the general public and among health care practitioners.